Preparation, thermal and phase evolution and functional properties of non-stoichiometric strontium-doped lanthanum manganite perovskite ceramics. Issue 11 (September 2017) - Colomer, M.T.; Ortiz, A.L.; López-Domínguez, V.; Alonso, J.M.; García, M.A.
Abstract: Powders of (La0.85 Sr0.15 )0.98 MnO3-δ (LSM85) and (La0.80 Sr0.20 )0.98 MnO3-δ (LSM80) perovskites have been synthesized and characterized in detail, and then sintered to evaluate their electrical and magnetic properties at low temperatures and at near room temperature. Microstructural observations/analyses after the dilatometric essays show that the perovskites have compositions that deviate from the nominal ones. Furthermore, magnetic characterization of both samples reveals a ferromagnetic behavior with a Curie temperature above 300 K for LSM80 and of 260 K for LSM85. In addition, LSM85 is insulator from 15 up to 300 K, whereas LSM80 is metallic up to 160 K and insulator up to 300 K. This significant discrepancy of behaviour is attributable to structural and compositional differences between the two perovskites.